Le cancer du sein et la chimiothérapie - BLAZREG, Djamila (My University, 2018)
Breast cancer is one of the most common cancers found among Algerian women, and worldwide, it is the leading cause of death in women. Breast cancer incidence rates vary by ethnicity and geographic location, this highlights the intervention of environmental factors, in addition to known risk factors such as, heredity, hormonal factors, age, and invaded (metastatic) lymph nodes. Our goal in this study is to first take stock of the epidemiology of breast cancer over the past two years and to perform, new correlations between known risk factors, and various anatomopathological parameters related to breast cancer such as the number of ganglia invaded by tumor cells. histological types and the effectiveness of chemotherapy on the patients affected. This study looked at 70 women with breast cancer. It shows that the most affected women are over 50 years old and the predominant and most common histological type is infiltrating ductal carcinoma (ICC) more than cases. Despite there are several types of treatments (chemotherapy, radiotherapy ... etc.) but still the number of patients have increased each year. Our goal is to do a theoretical study on oncology and breast cancer, demonstrated the importance of treatment on patients and talk about the effectiveness of chemotherapy and its performance in patients.
Keywords: Breast Cancer; ductal carcinoma infiltrating; lobular carcinoma infiltrating; Chemotherapy